Seasonal analysis of match load in professional soccer players: An observational cohort study of a Swiss U18, U21 and first team - Ammann, Linda; Altmann, Stefan; Ruf, Ludwig; Sperlich, Billy (Frontiers in Physiology, 2023)
The aim of this study was to quantify and compare various external match load measures in three age groups and leagues in male soccer (U18 in highest league of their age group vs U21 in fourth highest league vs 1st team in highest league). In this retrospective observational cohort study accelerations, decelerations, absolute and relative high-speed running as well as sprint distance, dynamic stress load, explosive distance, high intensity bursts total distance, high metabolic load (HML) distance, speed intensity, total distance, total time, and total loading were assessed in 416 individual player matches of 59 players. All these external load measures showed large inter-individual variability. At a group level, one-way ANOVAs or Kruskal-Wallis tests revealed statistically significant differences between the three teams for all measures analyzed (all p < .05), except accelerations. The 1st team displayed statistically significant higher dynamic stress load, explosive distance, HML distance, speed intensity, total distance and total loading compared to the two youth teams (all p < .05). The U18 featured statistically significant higher number of decelerations, absolute and relative high-speed running distance, HML distance, speed intensity, relative sprint distance, total distance, and total time than the U21, while for U21 higher dynamic stress load was observed than for U18 (all p < .05). Based on our data we conclude a routinely monitoring of match loads of different age groups and competitive settings to be required to i) provide an indication of what players need to be prepared for, ii) track the athletic and match evolution, and iii) individually tailor training programs allowing players to fulfill the short- and long-term sport-specific requirements.